A One‐Pot Strategy for the Synthesis of β‐Substituted Rhoda‐ and Irida‐Carbolong Complexes. Issue 15 (30th May 2022) - Xu, Binbin; Mao, Wei; Wu, Chengcheng; Li, Jinhua; Lu, Zhengyu; Luo, Ming; Liu, Liu Leo; Mao, Lingling; Chen, Dafa; Xia, Haiping
Comprehensive Summary: Starting from an organic multiyne, three steps are normally needed for the preparation of non‐ β ‐phosphonium functionalized rhoda‐ and irida‐carbolong complexes. Herein, a one‐pot strategy, by mixing a multiyne, a nucleophile, and RhCl(CO)(PPh3 )2 /AgBF4 or [Ir(CH3 CN)(CO)(PPh3 )2 ]BF4, was developed to achieve a series of β ‐functionalized rhoda‐ and irida‐carbolong complexes. The β ‐substituents in these complexes can be various C‐, N‐ and O‐centered groups, dependent on the nucleophiles used. This strategy provides a new convenient route to construct carbolong complexes, which is important for the further development of carbolong chemistry. Abstract : A one‐pot strategy, starting from a series of C ‐, N ‐ and O ‐centered nucleophiles, with the multiyne L and the corresponding metal precursors, was developed to achieve β ‐functionalized rhoda‐ and irida‐carbolong complexes, which are promising candidates for optoelectronic materials.